A Heuristic Approach for Inter-Facility Comparison of Results from Round Robin Testing of a Floating Wind Turbine in Irregular Waves - Sebastien Gueydon; Frances Judge; Eoin Lyden; Michael O’Shea; Florent Thiebaut; Marc Le Boulluec; Julien Caverne; Jérémy Ohana; Benjamin Bouscasse; Shinwoong Kim; Sandy Day; Saishuai Dai; et al. (Journal of Marine Science and Engineering, 2021)
This paper introduces metrics developed for analysing irregular wave test results from the round robin testing campaign carried out on a floating wind turbine as part of the EU H2020 MaRINET2 project. A 1/60th scale model of a 10 MW floating platform was tested in wave basins in four different locations around Europe. The tests carried out in each facility included decay tests, tests in regular and irregular waves with and without wind thrust, and tests to characterise the mooring system as well as the model itself. While response amplitude operations (RAOs) are a useful tool for assessing device performance in irregular waves, they are not easy to interpret when performing an inter-facility comparison where there are many variables. Metrics that use a single value per test condition rather than an RAO curve are a means of efficiently comparing tests from different basins in a more heuristic manner. In this research, the focus is on using metrics to assess how the platform responds with varying wave height and thrust across different facilities. It is found that the metrics implemented are very useful for extracting global trends across different basins and test conditions.